2016
DOI: 10.1155/2016/7891202
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol Promotes Schwann Cell Proliferation and Differentiation, Accelerating Early Remyelination in a Mouse Peripheral Nerve Injury Model

Abstract: Estrogen induces oligodendrocyte remyelination in response to demyelination in the central nervous system. Our objective was to determine the effects of 17β-estradiol (E2) on Schwann cell function and peripheral nerve remyelination after injury. Adult male C57BL/6J mice were used to prepare the sciatic nerve transection injury model and were randomly categorized into control and E2 groups. To study myelination in vitro, dorsal root ganglion (DRG) explant culture was prepared using 13.5-day-old mouse embryos. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 47 publications
0
12
1
Order By: Relevance
“…E2 also protects the brain from demyelination and stimulates remyelination by acting on oligodendrocytes, which may explain why women have better prognosis than men in multiple sclerosis ( Acs et al, 2009 ; Hirahara et al, 2009 ; Taylor et al, 2010 ; Kipp et al, 2012 ; Kumar et al, 2013 ; Patel et al, 2013 ). However, little is known about the role of E2 in Schwann cells myelination and remyelination in the PNS ( Zhu and Glaser, 2008 ; Chen et al, 2016 ). The present work found that E2 not only promotes SC myelination in a coculture model of SCs/DRG neurons, but also promotes SC remyelination in a rat sciatic nerve crush model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E2 also protects the brain from demyelination and stimulates remyelination by acting on oligodendrocytes, which may explain why women have better prognosis than men in multiple sclerosis ( Acs et al, 2009 ; Hirahara et al, 2009 ; Taylor et al, 2010 ; Kipp et al, 2012 ; Kumar et al, 2013 ; Patel et al, 2013 ). However, little is known about the role of E2 in Schwann cells myelination and remyelination in the PNS ( Zhu and Glaser, 2008 ; Chen et al, 2016 ). The present work found that E2 not only promotes SC myelination in a coculture model of SCs/DRG neurons, but also promotes SC remyelination in a rat sciatic nerve crush model.…”
Section: Discussionmentioning
confidence: 99%
“…17β-estradiol (E2), a nature estrogen in humans and rodents, plays diverse roles in physiological and pathological conditions in the nervous system ( Chaovipoch et al, 2006 ; Acs et al, 2009 ; Taylor et al, 2010 ). Recently, studies have suggested that E2 may regulate myelination and remyelination in both the central and peripheral nervous systems ( Melcangi et al, 2003 ; Schumacher et al, 2007 ; Zhu and Glaser, 2008 ; Chen et al, 2016 ). However, the mechanisms by which E2 regulates formation and maintenance of myelin sheath remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Both hormones are known to be neuroprotective and promote myelination, with estrogen (17β‐Estradiol) promotes nerve recovery in both the CNS and PNS (Schumacher et al, ; Zhu & Glaser, ). In the PNS, estrogen exerts its effects through the modulation of steroid nuclear receptors, which in turn upregulate the PI3K/AKT/mTOR signaling pathway and thereby promote the myelination (Chen et al, ). It is reported that PNS dorsal root ganglion neurons activate mTOR following a sciatic nerve injury and this activity enhances axonal growth capacity with the increased expression of growth‐associated protein, GAP‐43 (Abe, Borson, Gambello, Wang, & Cavalli, ).…”
Section: Steroid Hormonesmentioning
confidence: 99%
“…Steroid hormones, such as estrogen and progesterone, have been investigated for use in TPNI (Chen et al, 2016;Koenig et al, 2000;Nobakhti-Afshar et al, 2016), with both in vivo and in vitro evidence demonstrating the receptors for these hormones in the constituent cells of the peripheral nerve such as Schwann cells, dorsal root ganglia neurons, sensory and autonomic neurons (Magnaghi et al, 2009). Both hormones are known to be neuroprotective and promote myelination, with estrogen (17β-Estradiol) promotes nerve recovery in both the CNS and PNS (Schumacher et al, 2001;Zhu & Glaser, 2008).…”
Section: S Teroid Hormone Smentioning
confidence: 99%
See 1 more Smart Citation